Ч.Дашдаваагийн “Японы олзлогдогсод Монголд” номын шүүмж - Л.В, Курас; Б.Д, Цыбенов (Journal of International Studies, 2014)
English title: Book review of Ch.Dashdavaa’s “Japanese prisoners of war in Mongolia”